Densification of High Thickness C/C Composites by Chemical Vapor Infiltration. (2015) - Albano, M.; Pastore, R.; Delfini, A.; Micheli, D.; Volpini, F.; Marchetti, M.
Abstract: In the last decades the research on composite materials have been acquiring importance due to the possibility of increasing the material mechanical performances while contemporary decreasing both mass and volume of the structures. Composites are widely used in space vehicles and systems as structural materials, thermal blankets, thermal control and conformal coatings, adhesives, lubricants, etc. Exposure of composites to the space environment may result in different detrimental effects via modification of their chemical, electrical, thermal, optical and mechanical properties as well as surface erosion. The major degradation effects in composites are due to the exposure to atomic oxygen, vacuum ultraviolet, thermal cycling and combined effects during orbit period and plasma during re-entry phase. Among all, carbon-based ceramic composites are the most promising materials for space applications, due to their impressive thermal stability and lightweight. Carbon-Carbon (C/C) composites have already shown their extraordinary features in terms of high stability and excellent mechanical properties, almost unchanged at high temperatures. C/C is used also in engine applications such as nozzle throat section for launchers. The main feature for this application is the high resistance at high temperatures. In these applications high thickness composites are required, but one of the main criticalities is the uniformity of material and its final characteristics. Up to now, there's no standard for the manufacturing of high thickness C/C structures. In this paper a manufacturing method based on the chemical vapor infiltration (CVI) process is described, following each phase of the process from the preform preparation to the infiltration, and providing a detailedanalysis of the material densification.